1970
DOI: 10.4314/ejhs.v29i2.2
|View full text |Cite
|
Sign up to set email alerts
|

Magnitude and Factors Associated with Optimal Complementary Feeding Practices among Children Aged 6-23 Months in Bensa District, Sidama Zone, South Ethiopia

Abstract: BACKGROUND: Prevalence of optimal complementary feeding practices are lower than expected. Undernutrition contributes 35% of children mortality. Our study was aimed to assess magnitude and factors associated with optimal complementary feeding practices among children 6-23 months in Bensa Dstrict, Sidama Zone, South Ethiopia, 2016.METHOD: A community based cross sectional study was conducted from January to February 2016 in (8) randomly selected kebles found in Bensa District. Respondents were selected by using… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(16 citation statements)
references
References 7 publications
8
8
0
Order By: Relevance
“…e proportion of ACFP is unacceptably low in lowincome countries such as 23% in Bangladesh [13], 7.7% in Malawi [5], and 9.76% in Ethiopia [14]. In Ethiopia, the prevalence of ACFP among mothers who had IYC aged between 6 and 24 months was from 8.5 in a study held in Damot Weyde district to 70.3% in a study held in Debre Birhan town [15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…e proportion of ACFP is unacceptably low in lowincome countries such as 23% in Bangladesh [13], 7.7% in Malawi [5], and 9.76% in Ethiopia [14]. In Ethiopia, the prevalence of ACFP among mothers who had IYC aged between 6 and 24 months was from 8.5 in a study held in Damot Weyde district to 70.3% in a study held in Debre Birhan town [15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31].…”
Section: Introductionmentioning
confidence: 99%
“…Known independent predictors of ACFP are knowledge of mothers on IYC feeding practices, health education on IYC feeding practices, having repeated antenatal care (ANC) visits, having repeated postnatal care (PNC) visits, child age, maternal age, mothers' occupation, workload, mothers' educational status, birthplace, number of children, food secured in the household, and higher household wealth [16,18,20,21,[23][24][25][26][27][28][29]31].…”
Section: Introductionmentioning
confidence: 99%
“…A study from the Bensa District in the Sidama region reported similar numbers, with 48.2% of households being food secure and 52.1% experiencing some degree of food insecurity. They concluded that children from food secure families received a more optimal complementary feeding when comparing them to children from families experiencing food insecurity [ 24 ]. Another study from the Boricha district in Sidama reported that 82% experienced food insecurity over a year and showed seasonal variations with higher numbers of food-insecure households in March (69%) compared to September (50%) and December (38%) [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…about good patient management (18), especially during the COVID-19 pandemic. So patients who do not experience drug side effects are more likely to adhere to antiretroviral treatment than those who experience drug side effects (19).…”
Section: Side Effects Of Antiretroviral Therapymentioning
confidence: 99%
“…This qualitative research is about medication adherence during the covid- 19 The factors that influence patient adherence to taking ART are different during this covid-19 pandemic, namely the distance from which they live has an effect on patients wanting to take medication, so the role of NGOs in sending drugs is very important, according to the doctors approval, after the next 3 months the patient is required to come, this is never happened before the Covid-19 condition, Patients adherence are very dependent on the patient's self-awareness to live in the long term, the convenience has been provided by M Jamil Hospital by making it easy to send drugs to the patient's own address. This qualitative analysis using N vivo 12, which has now developed into N vivo 14 Patient recruitment is divided into two, namely obedient and non-compliant patients, but the patient's answers are almost the same.…”
Section: Strength and Limitation Of This Studymentioning
confidence: 99%